Penetrating Orbital Injury; a Case Report and Treatment Algorithm - Mehrdad Dehghanpour Barouj; Reza Tabrizi; Parsa Behnia; Mohammad Amir Alizadeh Tabrizi; Mahtab Kheirkhahi (Archives of Academic Emergency Medicine, 2020)
Penetrating orbital trauma (POT) consists of high and low velocity penetrating injuries that may lead to severe consequences such as visual impairment and globe tearing. It has been reported to make up 30% to 50% of all orbital injuries. POT requires a multidisciplinary approach due to complex orbital injury, which involves eye function, brain injury, and facial aesthetics. In this report, we presented a case of POT due to knife injury in which the knife blade was removed and bleeding was controlled, the patient’s general condition after surgery was good, but the vision of the right eye was lost.